Good practice criteria for childhood obesity prevention in kindergartens and schools—elaboration, content and use. (6th July 2018) - Kovacs, Viktoria A; Sarkadi-Nagy, Eszter; Sandu, Petru; Duleva, Vesselka; Spinelli, Angela; Kaposvari, Csilla; Hassapidou, Maria; Janssen, Dilani; Grochowska-Niedworok, Elżbieta; Messing, Sven; Martos, Eva
Abstract: Background: In accordance with the policy actions that address childhood overweight and obesity at European level and as a contribution to the EU Action Plan on Childhood Obesity 2014–20, a Joint Action on Nutrition and Physical Activity (JANPA) was established. As part of JANPA work package 6, an evaluation framework to identify good practices, targeting childhood obesity prevention in kindergartens and schools, was developed. This article describes the WP 6 JANPA framework of good practice criteria and its development, compares it to other frameworks and discusses its potential for future use. Methods: Based on the analysis of scientific literature, a set of 47 potential good practice criteria was drafted, that was then revised and complemented through a series of online Delphi consultations. Results: A final list of 48 good practice criteria (9 of which were rated as core criteria) was developed and grouped into three categories: intervention characteristics ( n = 17), implementation ( n = 17) and monitoring and evaluation ( n = 14). Conclusion: The identified JANPA framework of good practice criteria complements the existing frameworks by focussing on kindergarten- and school-based initiatives and provides guidance for evaluators, programme planners and decision makers bearing in mind that a one-size-fits-all approach is inadequate. To ensure the effectiveness of future practices, programme planners should endeavour to meet at least the nine JANPA core criteria.